Genetically Diverse Soybean Cyst Nematode–Resistant Full‐Sib Soybean Germplasm Lines AR4SCN, AR5SCN, AR6SCN, AR7SCN, and AR8SCN. Issue 1 (7th December 2017) - Cianzio, S. R.; Arelli, P. R.; Swaminathan, S.; Lundeen, P.; Gebhart, G.; Rivera-Velez, N.; Guilherme, S. R.; Soares, I. O.; Diers, B. W.; Knapp, H.; Westgate, M.; Hudson, M. E.
Abstract : Soybean [ Glycine max (L.) Merr.] yields will be protected by introgressing pathogen resistance, an objective of soybean breeding for pathogen resistance at Iowa State University (ISU). Germplasms AR4SCN (Reg. No. GP‐410, PI 684651), AR5SCN (Reg. No. GP‐411, PI 684652), AR6SCN (Reg. No. GP‐412, PI 684653), AR7SCN (Reg. No. GP‐413, PI 684654), and AR8SCN (Reg. No. GP‐414, PI 684655), are resistant to soybean cyst nematode (SCN, Heterodera glycines [HG] Ichinohe) HG type 0 (Race 3) and HG type 1.3.6.7 (Race 14). In 2007, ISU Projects 3722 of the Agronomy Department and Project 3384 of the Plant Pathology Department, the Iowa Agricultural and Home Economics Experiment Station, and the ISU Research Foundation released the lines. Each line is an F12:13 bulk of 60 agronomically uniform plants from the cross of the genetically diverse SCN parents PI 88788 and 'Columbia'. The cross made at the Isabela Substation, Puerto Rico, underwent generation advances in Puerto Rico and Iowa. Phenotyping/molecular characterizations of lines at Arelli's, Cianzio's and Diers' labs confirmed the presence of high copy numbers of the full‐length sequence repeat of the highly important major PI 88788‐type rhg1‐b gene, conferring high levels of SCN resistance on each germplasm. In Iowa, average seed yield of the maturity group (MG) II line AR4SCN was 57% of the check 'Dwight'. For MG III lines (AR5SCN, AR6SCN, AR7SCN, AR8SCN), yield was 77% of 'Macon'. The germplasms will serve in the development of SCN‐resistant genotypes adapted to northern US regions where SCN HG type 0 and/or 1.3.6.7 may be prevalent. Lines may also serve as research genetic stocks.